2021
DOI: 10.1155/2021/2801263
|View full text |Cite
|
Sign up to set email alerts
|

Activation of AdipoR1 with rCTRP9 Preserves BBB Integrity through the APPL1/AMPK/Nrf2 Signaling Pathway in ICH Mice

Abstract: Background. The disruption of the blood brain barrier (BBB) is the key factor leading to neurological impairment after intracerebral hemorrhage (ICH) injury. Adiponectin receptor 1 (AdipoR1) has an important effect contributing to the integrity of BBB. As a homologue of adiponectin, recombinant C1q/TNF-related protein 9 (rCTRP9) has neuroprotective effect in cerebrovascular diseases. The aim of this study was to investigate the protective effect of AdipoR1 activation with rCTRP9 on BBB integrity after ICH inju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Zhao W et al discovered that APPL1/AMPK/ Nrf2 signaling protected BBB (blood-brain barrier) integrity and enhanced neuronal function in ICH (intracerebral hemorrhage) mice. [29] However, the mechanism of ADIPOR1 in ASD is still unclear, and the relationship between ADIPOR1 and ASD can be explored in the aspect of blood-brain barrier. [30] Earlier research has demonstrated that the expression of genes related to the integrity of blood-brain barrier has changed in the brains of ASD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Zhao W et al discovered that APPL1/AMPK/ Nrf2 signaling protected BBB (blood-brain barrier) integrity and enhanced neuronal function in ICH (intracerebral hemorrhage) mice. [29] However, the mechanism of ADIPOR1 in ASD is still unclear, and the relationship between ADIPOR1 and ASD can be explored in the aspect of blood-brain barrier. [30] Earlier research has demonstrated that the expression of genes related to the integrity of blood-brain barrier has changed in the brains of ASD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that AdipoR1 could maintain the integrity of the blood-brain barrier through the APPL1/AMPK/Nrf2 signaling pathway [ 36 ]. And Nrf2 exerts its antioxidant role in cellular protection by regulating xCT expression [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Administration of CTRP9 treatment improved AdipoR1 and p-AMPK protein expression levels and decreased the protein expression levels of inflammatory cytokines and phosphorylated NFκB (P-NFκB), attenuating neuroinflammation via AdipoR1/AMPK/NFκB signaling pathway (Zhao et al, 2018 ). Activated AdipoR1 by CTRP9 treatment attenuated neuropathological deficits and improved BBB dysfunction by activating the APPL1/AMPK/Nrf2 signal axis in a collagenase-induced ICH mouse model (Xu et al, 2018 ; Zhao et al, 2021 ). This evidence suggested that CTRP9 could be recognized as an encouraging therapy to ameliorate BBB dysfunction in ICH patients.…”
Section: Potential Therapeutic Targets and Strategies Of Microglia-in...mentioning
confidence: 99%